William of Tyre, Translatio Imperii and the Genesis of the First Crusade: Or, the Challenges of Writing History. (History, 2022)
The article offers a contribution to wider dialogues on history creation and the analytical superstructures that influence how authors use the past to construct and legitimise identities tied to conquest and settlement. It takes as its case study the twelfth‐century Chronicon of the Jerusalemite writer William of Tyre, and his crafting of an account of the First Crusade that demonstrated the legal validity of the new Latin polities created in the Levant and Syria (the so‐called crusader states). It demonstrates his use of translatio imperii (translation of empire) to frame settlement as a continuation of Christian authority in the East. This work also marks the changing purpose of his writing away from a solely Eastern Latin audience towards promoting crusading from Europe. In paying attention to this shift, this article demonstrates how subsequent edits he made to his work(s) led to narrative dilemmas and discontinuities that spoke to the fragmented social and political value of crusading between the Latin East and Latin West. In other words, this article offers an important window onto not only the historians' craft, but also the value of incorporating premodern works into modern historiographical debates, especially those surrounding notions of European settler identities.